HIF-1α increases the osteogenic capacity of ADSCs by coupling angiogenesis and osteogenesis via the HIF-1α/VEGF/AKT/mTOR signaling pathway - Shuang Song; Guanhua Zhang; Xutao Chen; Jian Zheng; Xiangdong Liu; Yiqing Wang; Zijun Chen; Yuxi Wang; Yingliang Song; Qin Zhou (Journal of Nanobiotechnology, 2023)
Abstract Background Stabilization and increased activity of hypoxia-inducible factor 1-α (HIF-1α) can directly increase cancellous bone formation and play an essential role in bone modeling and remodeling. However, whether an increased HIF-1α expression in adipose-derived stem cells (ADSCs) increases osteogenic capacity and promotes bone regeneration is not known. Results In this study, ADSCs transfected with small interfering RNA and HIF-1α overexpression plasmid were established to investigate the proliferation, migration, adhesion, and osteogenic capacity of ADSCs and the angiogenic ability of human umbilical vein endothelial cells (HUVECs). Overexpression of HIF-1α could promote the biological functions of ADSCs, and the angiogenic ability of HUVECs. Western blotting showed that the protein levels of osteogenesis-related factors were increased when HIF-1α was overexpressed. Furthermore, the influence of upregulation of HIF-1α in ADSC sheets on osseointegration was evaluated using a Sprague–Dawley (SD) rats implant model, in which the bone mass and osteoid mineralization speed were evaluated by radiological and histological analysis. The overexpression of HIF-1α in ADSCs enhanced bone remodeling and osseointegration around titanium implants. However, transfecting the small interfering RNA (siRNA) of HIF-1α in ADSCs attenuated their osteogenic and angiogenic capacity. Finally, it was confirmed in vitro that HIF-1α promotes osteogenic differentiation and the biological functions in ADSCs via the VEGF/AKT/mTOR pathway. Conclusions This study demonstrates that HIF-1α has a critical ability to promote osteogenic differentiation in ADSCs by coupling osteogenesis and angiogenesis via the VEGF/AKT/mTOR signaling pathway, which in turn increases osteointegration and bone formation around titanium implants. Graphical Abstract